Draft Genome Sequence of the Extremely Halophilic Archaeon Halogranum salarium B-1(T) - Kim, Kwang Kyu (American Society for Microbiology, 2012)
Halogranum salarium is an extremely halophilic archaeon isolated from evaporitic salt crystals and belongs to the family Halobacteriaceae. Here, we present the 4.5-Mb draft genome sequence of the type strain (B-1(T)) of H. salarium. This is the first report of the draft genome sequence of a haloarchaeon in the genus Halogranum.